2005
DOI: 10.1002/jat.1111
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional compounds eliciting anti-inflammatory and anti-cholinesterase activity as potential treatment of nerve and blister chemical agents poisoning

Abstract: Certain organophosphorus (OP) nerve agents (e.g. soman) induce neuroinflammatory processes during acute poisoning. An increased level of typical inflammation markers was also observed in poisoning by alkylating agents such as sulfur mustard (HD). The therapeutic potential of new bifunctional compounds was investigated, eliciting activity of non-steroidal anti-inflammatory drug (NSAID) and anti-cholinesterase (anti-ChE) activity, as an antidotal treatment for both soman and HD poisoning in mice. Three bifunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…We found that post-treatment of zebrafish with these drugs significantly decreased the prevalence of brain toxicity, with the highest protection provided by MK-801 and caramiphen. The use of anti-inflammatory drugs has been proposed to counteract neuroinflammation during severe acute OP intoxication (Amitai et al 2006; Banks and Lein 2012; Dhote et al 2007; Spradling et al 2011). Post-treatment of the zebrafish with the anti-inflammatory agents ibuprofen and dexamethasone provided significant protection against brain toxicity, although this group of drugs was the least efficient of all tested treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We found that post-treatment of zebrafish with these drugs significantly decreased the prevalence of brain toxicity, with the highest protection provided by MK-801 and caramiphen. The use of anti-inflammatory drugs has been proposed to counteract neuroinflammation during severe acute OP intoxication (Amitai et al 2006; Banks and Lein 2012; Dhote et al 2007; Spradling et al 2011). Post-treatment of the zebrafish with the anti-inflammatory agents ibuprofen and dexamethasone provided significant protection against brain toxicity, although this group of drugs was the least efficient of all tested treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by increased expression of central neuroinflammatory genes (Levy et al, 2004). These observations have led to the development of a novel class of anti-inflammatory, anti-cholinesterase (anti-ChE) drugs that may have utility in treating nerve agent poisoning (Amitai et al, 2005). In a rat model of AChE inhibitor intoxication, markers of reactive oxygen species (ROS) and reactive nitrogen species (RNS) were found to be elevated in susceptible regions of brain within 15 min to 1 h of exposure (Gupta et al, 2007;Zaja-Milatovic et al, 2009); this was accompanied by dendritic damage to the hippocampus, a sensitive morphologic marker of neuronal injury (Gupta et al, 2007; see also Figure 50.1).…”
Section: Additional Acute Effects Of Nerve Agents On Brain Tissuementioning
confidence: 98%
“…Bifunctional derivatives have also been developed which successfully fulfill the dual tasks of inhibiting the catalytic activity of AChE and slowing the rate of Aβ aggregation by the PAS [71,72]. Other bifunctional gorge-spanning ligands have been developed which serve as dual inhibitors of AChE and monoamine oxidase [73], as dual anti-ChE and anti-inflammatory agents [74,75], or as dual anti-ChE and protectants against reactive oxygen species [76]. As mentioned in the Introduction, (-)-HupA acts as a neuroprotectant against a variety of agents, whether as an N-methyl-D-aspartate (NMDA) receptor antagonist or by other mechanisms [8].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%